Analysis of beta-carotene hydroxylase gene cDNA isolated from the American oil-palm (Elaeis oleifera) mesocarp tissue cDNA library - Bhore, Subhash J (Biomedical Informatics, 2010)
It is well known that the nutritional quality of the American oil-palm (Elaeis oleifera) mesocarp oil is superior to that of African oil-palm (Elaeis guineensis Jacq. Tenera) mesocarp oil. Therefore, it is of important to identify the genetic features for its superior value. This could be achieved through the genome sequencing of the oil-palm. However, the genome sequence is not available in the public domain due to commercial secrecy. Hence, we constructed a cDNA library and generated expressed sequence tags (3,205) from the mesocarp tissue of the American oil-palm. We continued to annotate each of these cDNAs after submitting to GenBank/DDBJ/EMBL. A rough analysis turned our attention to the beta-carotene hydroxylase (Chyb) enzyme encoding cDNA. Then, we completed the full sequencing of cDNA clone for its both strands using M13 forward and reverse primers. The full nucleotide and protein sequence was further analyzed and annotated using various Bioinformatics tools. The analysis results showed the presence of fatty acid hydroxylase superfamily domain in the protein sequence. The multiple sequence alignment of selected Chyb amino acid sequences from other plant species and algal members with E. oleifera Chyb using ClustalW and its phylogenetic analysis suggest that Chyb from monocotyledonous plant species, Lilium hubrid, Crocus sativus and Zea mays are the most evolutionary related with E. oleifera Chyb. This study reports the annotation of E. oleifera Chyb. ABBREVIATIONS: ESTs - expressed sequence tags, EoChyb - Elaeis oleifera beta-carotene hydroxylase, MC - main cluster